Gravity-selected Cluster Samples: A New Take on the Compton-y–Mass Relation - S. Andreon; M. Radovich (The Astrophysical Journal)
We investigate the scaling relation between the Compton- y parameter and mass in a gravity-selected sample of galaxy clusters, selected based on their gravitational lensing effects on background galaxies. Unlike intracluster medium (ICM)−selected samples, gravity-selected clusters do not require corrections for selection biases in ICM properties, such as Compton- y , since these properties are not used for selection. Our sample consists of 13 gravity-selected clusters with weak-lensing signal-to-noise ratios greater than 7 and redshifts in the range 0.1 <  z  < 0.4, drawn from the peak catalog of shear-selected clusters in M. Oguri et al. We determined spectroscopic redshifts using Sloan Digital Sky Survey spectroscopy, derived tangential radial profiles from Hyper Suprime-Cam shear data, and calculated cluster masses by fitting a Navarro, Frenk, & White profile. Compton- y measurements were obtained from Atacama Cosmology Telescope maps. Our sample reveals a broader scatter in the Compton- y –mass scaling relation compared to ICM-selected samples, even after accounting for selection effects and mass bias of the latter, which we find to be (1 −  b ) = 0.72 ± 0.09. Additionally, we identify a second population of clusters with unusually small Compton- y for their mass, which is absent in ICM-selected samples. This second population composes $1{3}_{-8}^{+10}$ % of the entire sample, with O19 currently being the only secure representative.